Effect of Penicillium extractsa on germination vigor in subsequent seedling growth of tomato (Solanum lycopersicum L.) - Nasim, Ghazala; Mushtaq, Sobia; Mukhtar, Irum; Khokhar, Ibatsam (Plant Breeding and Seed Science, 2012)
Penicillium spp. are well known to produce a variety of beneficial metabolites for plant growth and survival, as well as defend their hosts from attack of certain pathogens. In this study, effects of culture filtrate of different Penicillium spp. were tested on tomato seeds. On the whole, presoaking of seeds in filtrates of the nine Penicillium isolates tested, significantly increased seed germination when compared with the control seeds. Cultural extracts of P. expensum and P. billi were highly effective in growth promotion up to 90%. It was also observed that P. implicatum and P. oxlalicam significantly enhanced the root growth in tomato seedling as compare to other species. In case of shoot length, P. verrucosum (3.38), P. granulatum (2.81) and P. implicatum (2.62) were effective. However P. implicatum was quite promising to increase shoot and root length in tomato seedlings. Where as P. simplicissimium and P. citrinum were leas effective on seedling growth. The plant growth promoting ability of Penicillium strains may help in growth permotion in other plants and crops. Penicillium spp. are already known for producing mycotoxin and enzymes. Plant growth promoting ability of Penicillium spp will open new aspects of research and investigations. The role of Penicillium spp. in tomato plant growth requires further exploration.